Home Biogas Production using Homemade Bio-activator with Chicken Manure - Heru Surianto; Slamet Raharjo; Suci Wulandari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The previous experiment was obtained that homemade activator is the best activator to produce biogas by using food waste consist of vegetable, fruit and rice waste.  The current research is carried out by adding chicken manure as a co-activator. Chicken manure content rich in nitrogen can be significantly enhance biogas production. This study is expected to increase the biogas production. There are two processes conducted at the laboratory scale, batch and semi-continuous process. The batch process aim to activate bacteria. The ratio set at food waste/chicken manure, 2 : 1 of digester #1, 3 : 1 of digester #2, 4 : 1 of digester #3 and digester control using food waste only. Stage two aims to produce biogas by adding food waste for 6 days periodically.  The ratio is set at food waste/water, 1 : 2. The highest biogas yielded is digester 2 with a cumulative volume biogas 120.77 liters consist of 71.01% CH4, 26% CO2, 2.9% O2 and 0.088% H2S. The potential of methane gas produced is 0.87 kWh and methane volume per TS and VS at around 18.72 L/kg and 34.68 L/kg, respectively.